Overexpression of LcSABP, an Orthologous Gene for Salicylic Acid Binding Protein 2, Enhances Drought Stress Tolerance in Transgenic Tobacco - Li, Qian; Wang, Gang; Guan, Chunfeng; Yang, Dan; Wang, Yurong; Zhang, Yue; Ji, Jing; Jin, Chao; An, Ting (Frontiers in Plant Science, 2019)
Salicylic acid (SA) plays an essential role in the growth and development of plants, and in their response to abiotic stress. Previous studies have mostly focused on the effects of exogenously applied SA on the physiological response of plants to abiotic stresses; however, the underlying genetic mechanisms for the regulatory functions of endogenous SA in the defense response of plants remain unclear. In plants, salicylic acid binding protein 2 (SABP2), possessing methyl salicylate (MeSA) esterase activity, catalyzes the conversion of MeSA to SA. Herein, a SABP2-like gene, LcSABP, was cloned from Lycium chinense, which contained a complete open reading frame of 795 bp and encoded a protein of 264 amino acids that shared high sequence similarities with SABP2 orthologs from other plants. Overexpression of LcSABP enhanced the drought tolerance of transgenic tobacco plants. The results indicated that increased levels of LcSABP transcripts and endogenous SA content were involved in the enhanced drought tolerance. Physiological and biochemical studies further demonstrated that higher chlorophyll content, increased photosynthetic capacity, lower malondialdehyde content, and higher activities of superoxide dismutase, peroxidase, and catalase enhanced the drought tolerance of transgenic plants. Moreover, overexpression of LcSABP also increased the expression of reactive oxygen species (ROS)- and stress-responsive genes under drought stress. Overall, our results demonstrate that LcSABP plays a positive regulatory role in drought stress response by enhancing the endogenous SA content, promoting the scavenging of ROS, and regulating of the expression of stress-related transcription factor genes. Our findings indicate that LcSABP functions as a major regulator of the plant’s response to drought stress through a SA-dependent defense pathway.